Barriers and Strategies to Lifestyle and Dietary Pattern Interventions for Prevention and Management of TYPE-2 Diabetes in Africa, Systematic Review - Hirut Bekele; Adisu Asefa; Bekalu Getachew; Abebe Muche Belete (Journal of Diabetes Research)
Background. Diabetes mellitus is a major chronic illness in Africa that requires lifelong lifestyle interventions and pharmacological therapy. Lifestyle change is the most important aspect of diabetes care and includes diabetes self-management education and support, medical nutrition therapy, physical activity, smoking cessation counseling, and psychosocial care. Purpose. The purpose of this project was to review published articles that investigate lifestyle and dietary pattern interventions for diabetes prevention and management in Africa. Barriers to lifestyle interventions and strategies to overcome the barriers are also reviewed in this study. Methods. The article search was conducted in an electronic database search of PubMed, Google Scholar, and Cochrane Library. Studies were included if they were published between 2011 and 2019, if they were conducted in an African country, and were written in the English language. Results. Articles reviewed included several that examined the basic lifestyle and dietary pattern changes for all patients diagnosed with type 2 diabetes, on self-care behavior of type 2 diabetes patients, on the cost of diabetes in Africa, and on barriers for adherence to lifestyle and dietary changes in Africa, with strategies to address those barriers. Conclusion. Lifestyle interventions including regular physical exercise, weight management, and adherence to health care professionals’ recommendations on a healthy diet are the cornerstone in the prevention and management of diabetes in Africa. The main barriers to adherence were both systemic (population changes, poor access, western cultural influences, and low-quality healthcare) and personal (poverty and cost, educational status, and perceptions about the disease) in nature. The strategies for the barriers include health education programs, advocacy, and capacity building.